THE SEAMSTRESS of HOLLYWOOD BOULEVARD - McGraw, Erin, author 644289 (Boston, USA : Mariner Books, 2008)
"I couldn’t cook but I could sew. It would have been better the other way around." Trapped in Kansas at the turn of the twentieth century, Nell Plat is seventeen, unhappily married, and the mother of two baby girls. No reality could be further from her secret dreams of glamour and excitement, dreams that will tempt her to do the unthinkable and run away to the glittering wonderland of Los Angeles and the burgeoning motion picture industry. Lucky for Nell, her experience as a seamstress to the ladies of her Kansas town translates beautifully to work as a costumer to Hollywood in the Roaring Twenties. She renames herself Madame Annelle, and builds a new life for herself that looks so much more like the one she had always imagined. But a knock on the door threatens to rip apart the seams of her own carefully constructed costume, and Nell is forced to confront the legacy of her abandonment and deception. Can she rework the delicate fabric of her life?.